Age correlated histomorphological changes iu the cervix of buffalo (Bubalus bubalis) - UPPAL, VARINDER; ROY, K S (The Indian Journal of Animal Sciences, 2014)
Age correlated histomorphological changes in the cervix of buffalo revealed that the lamina epithelialis was simple cuboidal in neonatal calves which transformed into mucinogenic simple columnar in adult buffaloes. The epithelial height was more at the base of cervical folds than at its apex in all age groups. Tunica muscularis was made up of inner circular and outer longitudinally oriented smooth muscle fibres, which became 3 layered in prepubertal and adult animals. Collagen, reticular and elastic fibres were few and fine in neonates became coarser and denser with progression of age.